The Role of Sharia Governance in Fostering Customer Loyalty and Trust in Indonesian Islamic Banks: A Systematic Literature Review (2017-2024) - Fielnanda, Refky; Amalia, Euis; Hidayah, Nur (Review of Islamic Economics and Finance, 2024)
Purpose -This study aims to identify and examine the empirical literature of the past eight years (2017-2024) regarding the utilization of sharia governance in Islamic Banks in Indonesia and its impact on the trust and loyalty of Islamic bank customers.Methodology -The research methodology adopted was a systematic literature review conducted through literature exploration in the undergraduate google database with the help of Publish or Perish (PoP) software. A total of 640 articles addressing Islamic governance were initially identified and then screened using the covidence web based on inclusion and exclusion criteria and alignment with the research questions outlined in this systematic literature review, resulting in a final selection of 20 articles for review.Findings -The findings of the investigation explain that the dominant research approach used by scholars is quantitative, utilizing various statistical analysis techniques, including multiple linear regression analysis and Structural Equation Modelling (SEM). Islamic banking institutions in Indonesia have integrated sharia governance practices, utilizing various tools rooted in the principles of good corporate governance and sharia compliance. The results of this systematic literature review indicate that effective Islamic governance within Islamic banks in Indonesia has been proven to foster customer trust and loyalty.